In Vitro Evaluation of the Therapeutic Effects of Dual‐Drug Loaded Spermine‐Acetalated Dextran Nanoparticles Coated with Tannic Acid for Cardiac Applications. (22nd October 2021) - Torrieri, Giulia; Ferreira, Mónica P. A.; Shahbazi, Mohammad‐Ali; Talman, Virpi; Karhu, S. Tuuli; Pohjolainen, Lotta; Carvalho, Cláudia; Pinto, João F.; Hirvonen, Jouni; Ruskoaho, Heikki; Balasubramanian, Vimalkumar; Santos, Hélder A.
Abstract: Myocardial infarction results in a massive loss of cardiomyocytes (CMs). Unfortunately, current therapies are unsuccessful in replacing lost CMs, and thus, there is an urgent need for innovative approaches. Here, a nanosystem based on spermine‐acetalated dextran (AcDXSp) and encapsulating two drug compounds able to stimulate in vitro CMs proliferation is developed. The nanosystem is coated by deposition of a film constituted by tannic acid (TA) and Fe 3+ ions. The coating with TA increases the retention of the nanocarrier in cell co‐cultures of CMs and fibroblasts stimulated with transforming growth factor (TGF)‐β, due to the high affinity of TA for components of the cardiac extracellular matrix. The system exhibits biocompatibility toward primary CMs and induces their proliferation, as indicated by the two‐fold increase of CMs in the active cell cycle. At the same time, the presence of TA synergistically helps contrasting fibrosis by reducing profibrotic genes expression, such as collagen 1 and osteopontin, by approximately 80% compared to the control. Overall, the developed nanosystem demonstrates the capability to stimulate CMs proliferation and reduce fibrosis, showing potential benefits for future in vivo applications. Abstract : Delivery of compounds for the stimulation of cardiomyocytes proliferation shows promising therapeutic effects in vitro. A nanoparticulate system is developed combining the antifibrotic properties of the surface coating, together with the induction of cardiomyocytes proliferation, promoted by the drug payloads. The tannic acid coating also provides heart targeting properties.